Radiation Pattern Reconfigurable Antenna for IoT Devices - Zakaria Mahlaoui; Eva Antonino-Daviu; Miguel Ferrando-Bataller (International Journal of Antennas and Propagation)
Based on the characteristic mode theory, a versatile radiation pattern reconfigurable antenna is proposed. The analysis starts from two parallel metallic plates with the same and different dimensions. By means of two PIN diodes, the size of one of the parallel metallic plates can be modified and consequently the behavior of the radiation pattern can be switched between bidirectional and unidirectional radiation patterns. Moreover, a SPDT switch is used to adjust the frequency and match the input impedance. The reconfigurable antenna prototype has been assembled and tested, and a good agreement between simulated and measured results is obtained at 2.5 GHz band which fits the IoT applications.